2003
DOI: 10.4049/jimmunol.171.3.1581
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation Determines the Therapeutic Activity of Rituximab In Vivo

Abstract: Rituximab is an anti-CD20 chimeric mAb effective for the treatment of B-NHL. It can lyse lymphoma cells in vitro through both C- and Ab-dependent cellular cytotoxicity. The mechanism of action of rituximab in vivo is however still unclear. We have set up a new in vivo model in nonimmunodeficient mice by stable transduction of the human CD20 cDNA in the murine lymphoma line EL4. Animals injected i.v. with the EL4-CD20+ lymphoma cells died within 30 days with evident liver, spleen, and bone marrow involvement, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
330
4
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(355 citation statements)
references
References 48 publications
11
330
4
3
Order By: Relevance
“…In animal models, the activity of rituximab was completely abolished when administered to C1q-deficient knockout mice, demonstrating that complement activation is fundamental for rituximab efficacy (42). In the present study, no relation to the initial complement levels and renal response could be demonstrated (data not shown).…”
Section: Discussioncontrasting
confidence: 59%
“…In animal models, the activity of rituximab was completely abolished when administered to C1q-deficient knockout mice, demonstrating that complement activation is fundamental for rituximab efficacy (42). In the present study, no relation to the initial complement levels and renal response could be demonstrated (data not shown).…”
Section: Discussioncontrasting
confidence: 59%
“…CDC is clearly involved in the action of rituximab both in vitro and in preclinical mouse models (21,22,(32)(33)(34). Manches et al have also reported a correlation between in vitro sensitivity to CDC of various lymphoma subtypes and the likelihood of response to rituximab in the clinic (17).…”
Section: Discussionmentioning
confidence: 99%
“…Various in vitro and in vivo experiments have shown that elimination of CD20þ lymphoma cells by rituximab involves complement-dependent cytotoxicity (CDC; refs [16][17][18][19][20][21][22][23], direct induction of apoptotic signalling (24)(25)(26), as well as the recruitment of effector cells leading to antibody-dependent cell-mediated cytotoxicity (27). Nevertheless, the in vivo mechanism of action of and resistance to rituximab are not fully understood (28).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the susceptibility of all the cells examined for ADCC did not correlate with the clinical response to the Ab, whereas the in vitro cell-sensitivity to CDC was found to be the best predictor of the in vivo effect of Rituximab [15]. The important role of CDC in mediating the therapeutic effect of Rituximab was supported by the finding that the growth of a murine lymphoma transfected with CD20 was inhibited by Rituximab in complement-sufficient but not in C1q-deficient mice [16].…”
Section: Introductionmentioning
confidence: 99%